Case reportPatchy alopecia areata sparing gray hairs: a case series - Jia, Wei-Xue; Mao, Qiu-Xia; Xiao, Xue-Min; Li, Zhi-Liang; Yu, Rui-Xing; Li, Cheng-Rang (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Alopecia areata is an unpredictable, non-scarring hair loss condition. Patchy alopecia areata sparing gray hairs is rare. Here we present 4 cases with patchy non-scarring hair loss, which attacked pigmented hairs only and spared gray hairs. It should be differentiated from vitiligo, colocalization of vitiligo and alopecia areata, and depigmented hair regrowth after alopecia areata.